X-ray diffraction for probing free energy profiles and self-diffusivity of gases in metal–organic frameworks. Issue 36 (1st September 2022) - Chiou, Da-Shiuan; Chuang, Yu-Chun; Chang, Chung-Kai; Hsu, Cheng-Hsun; Lin, Li-Chiang; Kang, Dun-Yen
Abstract : This paper presents a novel methodology for measuring the free energy profiles and the self-diffusivity of gases in crystalline microporous materials. Abstract : This paper presents a novel methodology for obtaining the free energy profiles and the self-diffusivity of gases in crystalline microporous materials. The proposed approach is based on X-ray diffraction performed in situ on powder rather than single crystal samples. As proof of concept, we derive the self-diffusion properties of CO2 and CH4 in a metal–organic framework, CAU-10-H. The free energy profiles and self-diffusivity values acquired experimentally using the proposed methodology match those obtained through molecular simulations. This XRD-based methodology can be used for the design of MOFs for membrane gas separation.